Adamts18 Deficiency Causes Spontaneous SMG Fibrogenesis in Adult Mice. (February 2022) - Yang, N.; Zhang, Q.; Ye, S.; Lu, T.; Sun, M.; Wang, L.; Wang, M.; Pan, Y.H.; Dang, S.; Zhang, W.
Chronic sclerosing sialadenitis of the submandibular gland (also known as Küttner tumor) is characterized by concomitant swelling of the submandibular glands secondary to strong lymphocytic infiltration and fibrosis. The pathogenesis of this disease has been unclear, but it is associated with immune disorders. ADAMTS18 is a member of the ADAMTS superfamily of extracellular proteinases. In this study, we showed that Adamts18 is highly expressed in submandibular salivary gland (SMG) during embryonic development and decreases but is retained in adult SMG tissue in mice. Adamts18 deficiency led to reduced cleft formation and epithelial branching in embryonic SMG before embryonic day 15.5 in mice. No significant histologic changes in the later stages of branching or the morphology of SMG were detected in Adamts18 −/− mice. However, Adamts18 deficiency causes spontaneous SMG fibrogenesis and fibrosis in adult mice. At 8 wk of age, Adamts18 −/− mice began to manifest the first signs of pathologic changes of mild fibrosis and CD11b + cell infiltration in SMG tissues. At ≥8 mo, all male and female Adamts18 −/− mice developed unilateral or bilateral SMG scleroma that is similar to patients with chronic sclerosing sialadenitis of the submandibular gland. Adamts18 −/− mice also showed secretory dysfunction and severe dental caries. Histologically, SMG scleroma is characterized by progressive periductal fibrosis, acinar atrophy, irregular duct ectasis, and dense infiltration of IgG-positive plasma cells. A significant infiltration of CD4 + T lymphocytes and CD11b + monocytes and macrophages was also detected in the SMG scleroma of Adamts18 −/− mice. The levels of TGF-β1, IL-6, and IL-33 were significantly increased in Adamts18 −/− SMGs, which induces chronic inflammation and myofibroblast activation, ultimately leading to fibrosis. This study indicates that Adamts18 regulates the early branching morphogenesis of embryonic SMG and plays a role in protecting from spontaneous SMG fibrogenesis via modulating local inflammation, autoimmune reaction, and myofibroblast activation in adult mice.